Pengembangan game edukasi berbasis android tentang domain teknologi pendidikan - Ujang Nendra Pratama; Haryanto Haryanto (Universitas Negeri Yogyakarta, 2017)
Penelitian ini bertujuan untuk menghasilkan produk gameAndroid berisi materi Domain TP yang layak sebagai alternatif media belajar bagi mahasiswa prodi TP FIP UNY. Nilai kelayakan diketahui melalui penilaian ahli, calon pengguna, dan daya guna pembelajaran. Pengembangan produk dilaksanakan melalui lima tahap utama: studi pendahuluan, perencanaan, perancangan, pengembangan, dan evaluasi. Pengumpulan data dilakukan dengan wawancara studi pendahuluan, identifikasi gaya belajar, validasi ahli, validasi calon pengguna, serta pengujian eksperimen. Jumlah responden terdiri dari satu dosen pengampu, dua ahli media dan materi, serta 60 mahasiswa. Hasil penelitian menunjukkan bahwa produk yang dikembangkan telah memenuhi kriteria kelayakan dari validasi media, materi, calon pengguna, serta uji daya guna. Penilaian ahli materi masuk dalam kategori sangat layak, sedangkan ahli media dan calon pengguna masuk dalam kategori layak. Produk juga terbukti memiliki kelayakan daya guna berdasarkan perbedaan rerata nilai pretes dan postes kedua kelompok uji, sehingga perbandingan nilai gain menunjukkan perbedaan yang signifikan.Kata kunci: game edukasi, domain TP, Android THE DEVELOPING ANDROID-BASED EDUCATIONAL GAME ON EDUCATIONAL TECHNOLOGY DOMAINSAbstractThe study aims to produce an Android game on EduTech Domain materials which appropriate as an alternative learning media for students of Educational Technology in FIP UNY. Appropriateness was known through assessment of experts, future users, and learning usability. The product development procedure implemented through five main stages: preliminary study, planning, design, development, and evaluation. Data collection was done by preliminary study interview, learning style identification, expert validation, future users validation, and experimental testing. The participants consisted of a supporting lecturer, two experts of media and subject matter, seven students, and also 60 students. The result showed that the developed product has been able to reach appropriateness criterion from the validations of media, subject matter, future users, and usability testing. Subject matter experts assessment included in the very appropriate category, while media experts and future users included in the appropriate category. The product are also had usability appropriateness evidently based on differences between the mean values of pre-test and post-test of both test group, so that the comparison of gain value showed a significant differences.Keywords: educational game, EduTech domains, Android